Crispant analysis in zebrafish as a tool for rapid functional screening of disease-causing genes for bone fragility - Sophie Debaenst; Tamara Jarayseh; Hanna De Saffel; Jan Willem Bek; Matthieu Boone; Ivan Josipovic; Pierre Kibleur; Ronald Y Kwon; Paul J Coucke; Andy Willaert (eLife, 2025)
Heritable fragile bone disorders (FBDs), ranging from multifactorial to rare monogenic conditions, are characterized by an elevated fracture risk. Validating causative genes and understanding their mechanisms remain challenging. We assessed a semi-high throughput zebrafish screening platform for rapid in vivo functional testing of candidate FBD genes. Six genes linked to severe recessive osteogenesis imperfecta (OI) and four associated with bone mineral density (BMD) from genome-wide association studies were analyzed using CRISPR/Cas9-based crispant screening in F0 mosaic founder zebrafish. Next-generation sequencing confirmed high indel efficiency (mean 88%), mimicking stable knock-out models. Skeletal phenotyping at 7, 14, and 90 days post-fertilization (dpf) using microscopy, Alizarin Red S staining, and microCT was performed. Larval crispants showed variable osteoblast and mineralization phenotypes, while adult crispants displayed consistent skeletal defects, including malformed neural and haemal arches, vertebral fractures and fusions, and altered bone volume and density. In addition, aldh7a1 and mbtps2 crispants experienced increased mortality due to severe skeletal deformities. RT-qPCR revealed differential expression of osteogenic markers bglap and col1a1a, highlighting their biomarker potential. Our results establish zebrafish crispant screening as a robust tool for FBD gene validation, combining skeletal and molecular analyses across developmental stages to uncover novel insights into gene functions in bone biology.